A dynamic weighted algorithm for multiple radar fusion in an active protection system. (October 2021) - Wang, Jinli; Song, Haiping; Chen, Riming; Zhang, Yaning
The threat detection system based on short-range radars is an essential part of the active protection system (APS) of armored vehicles. The multi-radar data fusion problem is one of the crucial issues in the APS. Firstly, a general algorithm for multi-radar coordinates transformation is given. Then, based on the weighted fusion model and the trajectory characteristics of targets in the APS, a real-time dynamic weighting factor derivation algorithm is proposed. The algorithm is simulated in a dual-radar threat tracking and ballistic prediction scenario. The results prove the correctness and effectiveness of the algorithm.